Adäquate Antiinfektivatherapie: Bedeutung der individuellen Dosierung und Applikation = Adequate anti-infective treatment : importance of individualdosing and application - Brinkmann, Alexander; Richter, Daniel; Weigand, Markus A. (Der Anaesthesist, 2018)
Sepsis-induced changes in pharmacokinetic parameters are a well-known problem in intensive care medicine. Dosing of antibiotics in this setting is therefore challenging. Alterations to the substance-specific kinetics of anti-infective substances have an effect on the distribution and excretion processes in the body. Increased clearance and an increased distribution volume (Vd) and particularly compromized organ function with reduced antibiotic elimination are often encountered in patients with sepsis. Renal replacement treatment, which is frequently used in intensive care medicine, represents a substantial intervention in this system. Current international guidelines recommend individualized dosing strategies and adaptation of doses according to measured serum levels and pharmacokinetic/pharmacodynamic (PK/PD) parameters as concepts to optimize anti-infective therapy in the critically ill. Likewise, the recommendation to adjust the administration form of beta-lactam antibiotics to prolonged or continuous infusion can be found increasingly more often in the literature. This article reviews the background of the individual dosing in intensive care patients and their applicability to the clinical routine.